1707. Invasive Pulmonary Aspergillosis in Patients with Severe Fever with Thrombocytopenia Syndrome - Bae, Seongman (Open Forum Infect Dis, 2019)
BACKGROUND: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging tick-borne disease often accompanied by immune catastrophic course and subsequent fatal outcome. More than 90% of patients with SFTS had leukopenia and about one-third of those need the admission of intensive care unit (ICU) during the hospital course. So, there has been growing concern about the complications such as invasive pulmonary aspergillosis (IPA) in critical SFTS patients. We thus investigate the incidence and clinical characteristics of IPA in patients with SFTS. METHODS: All patients who were confirmed as SFTS in a tertiary care hospital, Seoul, South Korea, between January 2013 and October 2018 were enrolled. The modified AspICU algorithm was used to identify cases of putative invasive pulmonary aspergillosis (PIPA) and discriminate these invasive diseases from colonization. RESULTS: Of the 45 PCR-confirmed SFTS patients, 16 (36%) received ICU care. Of these 16 patients, 9 (56%) developed PIPA during hospitalization. The median duration from admission to the first evidence of PIPA was 8 days (range, 2–11 days). None of the PIPA cases met the revised EORTC/MSG criterion. Septic shock and corticosteroid administration preceded more frequently in PIPA group than non-PIPA group (100% vs. 19%, P < 0.0001 and 67% vs. 14%, P = 0.003, respectively). Patients complicated by PIPA showed significantly higher mortality than non-PIPA patients (44% vs. 8%, P = 0.048 by log-rank test). Mortality was lower in patients with PIPA who received antifungal treatment (17% [1/6]) than in those with PIPA who did not (100% [3/3]) (log-rank test, P = 0.002). CONCLUSION: More than half of patients with SFTS in ICU were complicated by IPA during early hospital course. Cautious scrutiny for IPA in patients with SFTS followed by early appropriate antifungal therapy for IPA is needed. [Image: see text] [Image: see text] [Image: see text] [Image: see text] [Image: see text] DISCLOSURES: All authors: No reported disclosures.